PENGARUH PREDIKET HAJI MABRUR TERHADAP MOTIVASI MANASIK CALON JAMAAH HAJI - JAPERI JAPERI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
This study aims to see the influence of the title of "hajj mabrur" to the motivation of hajj manasik. The study was conducted in the city of Padang, West Sumatra. This paper is a literature study. The study found that mabrur prediket strongly influence the motivation of manasik.